Autoformation et réseaux virtuels - Pascal Cyrot; Christophe Jeunesse (Centre National d'Enseignement à Distance, 2012)
Largely democratized now, social networks are virtual daily learning spaces. The individual or collective self-learners rush in these new worlds, suggesting at first sight scarcity or even lack of social learning. In continuation of a study on conventional self-teaching sociability (Cyrot, 2009), we investigated this new area by taking for corpus the written records to be found in comments on Youtube videos as possible sources of learning. Besides the importance of virtual social interactions connected with self-teaching, this exploratory study describes the presence of virtual sociabilities during the three stages of an episode of self-teaching (triggering, phase of self-learning, conclusion).